Complications in neuroanesthesia - Prabhakar, Hemanshu (Academic Press is an imprint of Elsevier, 2016)
Complications in Neuroanesthesia focuses on complications that may arise related to neuroanesthesia practice and discusses its various causes. Each complication is written as a separate chapter, and the pathophysiology and mechanisms of each complication, as well as measures for diagnosis, treatment and prevention are discussed. Towards the end of the book, several case scenarios are provided to the readers that challenge readers to diagnose the possible complication for each case. Chapters include brain and spinal cord problems, cardiovascular and hematological problems, and nerve and muscle problems. Written in a standard format, Complications in Neuroanesthesia provides quick and easy access to understanding problems in neuroanesthesia. It provides insight into all possible complications occurring during perioperative management of neurosurgical and neurologic patients. It is useful for trainees, clinicians, and researchers in the fields of neurosurgery, neurocritical care, and neurology by providing an understanding of preventable mishaps that may occur in neurosurgical or neurologic patients.